Implementation of drone based delivery of medical supplies in North-East India: experiences, challenges and adopted strategies - Aggarwal, Sumit; Gupta, Prakamya; Mahajan, Nupur; Balaji, Sivaraman; Singh, Khangembam Jitenkumar; Bhargava, Balram; Panda, Samiran (Frontiers in Public Health, 2023)
Timely delivery of medical supplies is essential in the healthcare sector, which is hampered by factors such as poor transportation network, traffic and adverse environmental conditions. Alternatively, drone operations can leapfrog the last mile logistic solutions in hard-to-reach terrains. The present paper elucidates the implementation process of drone-based delivery of medical supplies, operational challenges and innovations adopted by scientists in Manipur and Nagaland. Three districts, Bishnupur, Imphal West and Churachandpur from Manipur and two districts, Mokokchung and Tuensang from Nagaland, were selected for the study. Regulatory and ethical approvals and coordination with state health and administrative authorities were accorded. Implementation and operational challenges faced by the research team were recorded elaborately in the field diaries and assessed qualitatively. The experiences encountered by the team for case-to-case based permission and coordination with the central and state aviation authorities, district administration and health authorities were observed. The drone-related technical and logistic challenges were identified as the deployment of suitable drones, payload capacity, time management for operations, and transportation of drones. The officials adopted mitigation strategies to overcome field-based challenges. Drone-based deliveries of medical supplies are proving to be time efficient, however, overcoming operational challenges could provide an effective long-term deployment strategy.